Effect of Artificial Tear Supplements on Vision. - Dhakal, Krishna Prasad (Optometry & Visual Performance, 2020)
Background: Artificial tear supplementation is the first-line treatment in dry eye disease (DED) and many other ocular disease conditions. Some clinicians prefer drops, while others choose gels to help their patients. It is observed that patients complain of decreased vision with gel but improved performance with drops. This study was carried out to compare visual acuity (VA) and contrast sensitivity (CS) before and after instillation of artificial tear drops and tear gels. Methods: A prospective study was performed using 60 subjects (120 eyes). Tear film status was checked by doing tear breakup time (TBUT) and the Schirmer test. Subjects having previously diagnosed dry eyes were not included in the study. VA and CS were assessed pre- and post-instillation of artificial tear drop and tear gel. Results: The mean VAs pre- and post-instillation of the tear drop were 0.0168 ± 0.1993 LogMAR and 0.0090 ± 0.2126 LogMAR, respectively (z=-0.4287, p=0.3341), which were statistically insignificant. VA after the instillation of tear gel was significantly decreased, with mean values of 0.1600 ± 0.1839 LogMAR (z=9.6, p<0.000). CS values pre- and post-instillation of the tear drop were 1.7813 ± 0.1466 and 1.7638 ± 0.1411 (z=-1.307, p=0.9045), respectively, which were statistically insignificant. CS after tear gel reduced significantly, with a mean value of 1.6887 ± 0.1533 (z=-6.97, p<0.0001). The tear film status between males and females were not significant, both quantitatively (Schirmer's test) and qualitatively (TBUT) (z =-0.2148, p=0.8299 and z=-0.7723, p=0.4399). Conclusion: VA and CS remain the same after instillation of tear drops, allowing use at any time of the day. Artificial tear gel decreased visual function. For those who require fine visual functions (VA and CS), tear gel is not a good option for daytime treatment.